Pola Komunikasi Ibu Tunggal Dalam Proses Perkembangan Karakter Anak Studi Kualitatif pada Mahasiswa/i Ilmu Komunikasi FISIP UNSIKA Angkatan 2020 - Lestari, Rani Rizka; Yusup, Eka; Oxcygentry, Oky (CV. ITTC INDONESIA, 2024)
The high rate of divorce in Indonesia raises new concerns for parents in educating their children. The integrity of family members is essential in fostering positive character development in children. For a mother, fulfilling two roles within the family is not an easy task. The application of different communication patterns can lead to varying character development in children. This study aims to identify the communication patterns employed by single mothers in the character development of their children, as well as to understand the obstacles faced by single mothers in communicating with their children. This research uses a qualitative method with a phenomenological study approach. The theory used in this research is symbolic interactionism. Data collection was conducted through observation, in-depth interviews, and literature studies. The findings indicate that there are several different communication patterns implemented by single mothers in educating and shaping their childrens positive character. The obstacles faced by each family vary, but each family strives to maintain effective communication within the family.